2010
DOI: 10.1007/s11999-010-1296-6
|View full text |Cite
|
Sign up to set email alerts
|

Two-stage Exchange Knee Arthroplasty: Does Resistance of the Infecting Organism Influence the Outcome?

Abstract: Background Periprosthetic joint infection after TKA is a challenging complication. Two-stage exchange arthroplasty is the accepted standard of care, but reported failure rates are increasing. It has been suggested this is due to the increased prevalence of methicillin-resistant infections. Questions/purposes We asked the following questions:(1) What is the reinfection rate after two-stage exchange arthroplasty? (2) Which risk factors predict failure? (3) Which variables are associated with acquiring a resistan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
83
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 115 publications
(91 citation statements)
references
References 20 publications
5
83
1
Order By: Relevance
“…Two-stage prosthesis exchange with intervening placement of an antibiotic-impregnated polymethylmethacrylate (PMMA) spacer enables local delivery of high concentrations of antibiotic, preserves joint space and joint motion, and maintains patient mobility [5,12]. However, it is not uniformly successful.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Two-stage prosthesis exchange with intervening placement of an antibiotic-impregnated polymethylmethacrylate (PMMA) spacer enables local delivery of high concentrations of antibiotic, preserves joint space and joint motion, and maintains patient mobility [5,12]. However, it is not uniformly successful.…”
Section: Introductionmentioning
confidence: 99%
“…Despite best current practices, investigations have documented reinfection rates as much as 33% [8, 12, and 20]. Recurrence of infection may be more frequent in the setting of resistant organisms such as methicillin-resistant Staphylococcus aureus (MRSA) and methicillin-resistant Staphylococcus epidermidis or in cases requiring multiple prior open procedures [8,11,12,15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…If we had excluded our patients with MRSA infections, our rate of infection control would increase from 70% (19 of 27) to 76% (19 of 25), and the findings would appear more comparable. Other authors have indicated that regardless of the treatment modality, whether I&D [3,7] or one-stage [16] or two-stage exchange [17,19,21,36], infections caused by the more virulent organisms have a higher failure rate. Although our study was underpowered to draw definitive conclusions regarding implant retention based on organism, we are also concerned whether cementless single-stage exchange arthroplasty can control MRSA infection supporting prior authors' results [3,7,14,18] that these patients may best be treated with a two-stage exchange arthroplasty.…”
Section: Discussionmentioning
confidence: 99%
“…Drs. Kendoff and Gehrke: There seems to be more and more clinical evidence from the United States showing a relative lower success rates (< 75%) in terms of infection control in multidrug-resistant and culturenegative PJI, especially in the knee [7,8]. Furthermore one current report from the United States describes a high risk of associated mortality (7%) in the two-stage approach for PJI of the hip, with many deaths occurring even before the point of reimplantation [2].…”
Section: Clinical Faceoffmentioning
confidence: 99%